The Impact of Transformational Leadership and Work Motivation on Employee Performance in the Production Department of PT. TJ Forget Indonesia - Endrian, Muhammad; Jamaludin, Asep; Nandang, Nandang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
The research was conducted to assess the effect of Transformational Leadership Style and Motivation on the performance of employees at PT TJ Forget Indonesia. A quantitative research method was applied through the use of a survey. The sample consisted of the entire employee population, totaling 100 individuals. Primary data was collected for the study, and the data analysis employed multiple regression techniques using SPSS 26.0 software. The study's results revealed that the employees at PT TJ Forget Indonesia rated the company's Transformational Leadership Style as very good. Employee motivation also achieved a very high rating, while overall employee performance was categorized as good. The analysis demonstrated that both Transformational Leadership Style and Motivation jointly have a significant effect on employee performance. On a separate analysis of each factor, it was found that Transformational Leadership Style alone significantly influences employee performance. Likewise, employee motivation was shown to have a positive and significant impact on performance when analyzed independently